Sinonasal Polyposis and Fungus: A growing relationship - Siddiqui, Atif Hafeez; Sheikh, Arslan Ahmed; Khan, Tariq Zahid; Marfani, M. Saleem; Ali, Arif (International Journal of Endorsing Health Science Research, 2014)
Objectives: To determine the frequency of underlying fungus in nose and paranasal sinuses in patients present with nasal polyposis. Methodology: A total of 324 patients presented with nasal polyps were included in this study. Data collected from all the patients admitted in ENT department with diagnosis of nasal polyposis. All the relevant information about their presenting symptoms was recorded in a proforma. Post operatively the removed material was sent for histopathology and fungal culture. Later the findings of biopsy and culture reports were also recorded and analysed. Results: Out of 324 patients 159 were males and 165 were females. Underlying fungus was present in 226(69.75%) and out of them, 102(45.13%) were males and 124(54.86%) were females with a P value of 0.039. The mean age was 25.95 ± 9.32 (15-45) years for the patient with fungus. Aspergillus was the commonest organism found. Conclusion: Underlying fungus was found in a significantly high number of patients presented with nasal polyps and Aspergillus was the commonest organism found.